State and Revolution in Finland - Alapuro, Risto (Historical Materialism Book Series, 2018)
By analysing the experience of Finland, Risto Alapuro shows how upheavals in powerful countries shape the internal politics of smaller countries. This linkage, a highly topical subject in the twenty-first century world, is concretely studied by putting the abortive Finnish revolution of 1917-18 into a long historical and a broad comparative perspective. Readership: Institutes and academic libraries whose specialties include modern European political history, notably (1) the Nordic countries and (2) Eastern Europe.